Perencanaan Perencanaan Strategis Sistem Informasi Dalam Upaya Meningkatkan Kualitas Lulusan Menggunakan Alat Ukur IT Balanced Scorecard - Muhamad Ryzki Wiryawan; Ricky Rohmanto; Ida Rapida Djachrab; Tria Alma Dewi (Masoem University, 2026)
The utilization of information systems and information technology (IS/IT) has become a strategic factor in improving the quality of educational services and graduate outcomes in vocational education institutions. SMK Negeri 1 Cimahi, as a competency-based educational institution with a strong focus on IT, requires an information system strategic planning that is aligned with the organization’s business strategy in order to produce graduates who are competent and competitive in the labor market and industry. This study aimed to develop an information system strategic planning framework to improve graduate quality using the IT Balanced Scorecard as a measurement tool. The research employed a case study method with a descriptive qualitative approach, involving literature review, document analysis, observation of business processes, and strategic analysis using SWOT, value chain analysis, critical success factors, and the IT Balanced Scorecard. The results showed that the information system strategic planning produced ten priority IS strategies, which were grouped into two main focuses: IT service development and IT optimization. These findings indicate that improving graduate quality can be more effectively achieved through strengthening IS services that directly support the educational process. The output of this study is a blueprint for information system strategic planning that can serve as a reference for sustainable IS/IT development in vocational education institutions.